PEMETAAN GEOSPASIAL RISIKO BANJIR DI SUB-DAS GUNTING, JOMBANG JAWA TIMUR - Arbi Tri Kuswardhana; entin hidayah; Retno Utami Agung Wahyono (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2023)
Floods are the most recurring natural disasters and impact human life, causing a severe economic downturn. The level of flood risk is a function of hazard and vulnerability. Flood risk-prone areas need to be identified to reduce the flood risk level. This study aims to assess flood risk based on spatial analysis results with Geographic Information Systems (GIS). The flood hazard map is built from remote sensing-based data in the form of a digital elevation model (DEM) applied using the frequency ratio weighting (FR) technique. Vulnerability maps are generated from social, economic, physical, and environmental data applied through techniques overlays weighted using the analytical hierarchy process (AHP). The resulting risk map shows that 21.93% and 6.40% of the total area are at a very high and high level of flood risk. This map is very useful for planning the flood management.